Slovenski večbesedni leksemi z vidika slovaropisja - Petric, Špela (Lingua Slovenica, 2018)
The present monography entitled A Study of Slovenian Multi-Word Lexemes from a Lexicographical Perspective provides a typology of newer nominal multi-word lexemes with potential terminological meaning, based on the theory of Russian linguist N. M. Shanskiy which brings four precisely defined levels of semantic merger of their components. The analysis of individual components of multi-word lexemes from a morphological, syntactic and semantic perspective reveals typological tendencies of nominal multi-word lexemes which occurred especially in the last twenty years.The typology takes into account the causal relationship between the level of semantic transfer (of the components) of a multi-word lexeme on the one hand and the level of semantic merger of components of a multi-word lexeme and related lexicalization of a multi-word lexeme on the other hand, which is also reflected in the restricted collocability of their components. Lexicalized or non-lexicalized metaphorical and metonymic semantic transfers are contributing to the new semantic and syntactic combinations of individual words in the phrase, to the consequent integration of their meanings to form a single meaning of the multi-word lexeme and thus to a higher level of lexicalization and semantic firmness of a multi-word lexeme.